1985
DOI: 10.1017/s0043174500083843
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea (Vigna unguiculata) Seed Protein Response to Glyphosate

Abstract: Electrophoretic analysis of storage protein accumulation in developing cowpea [Vigna unguiculata(L.) Walp. ‘Mississippi Purple’] seed indicated that a large increase in protein content per seed occurred between 10 and 11 days after flowering (DAF). Polypeptides with molecular weights of 54, 49, and 41 kilodaltons (kD) accumulated first, and one with a molecular weight of 59 kD appeared 2 days later at 13 DAF. Treatment of plants with glyphosate [N-(phosphonomethyl)glycine] when pods were 7 and 10 DAF prevented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…This pat-tern of decreased seed germination was observed when herbicides were applied late season but before seed physiological maturity (Azlin and McWhorter 1981;Whigham and Stoller 1979). Previous studies have shown that glyphosate, when applied to plants during seed fill, inhibits seed development by reducing the supply of aromatic amino acids (Cerdeira et al 1985). Similar studies, to our knowledge, have not been conducted for cyclohexanedione herbicides.…”
Section: Seed Yieldsupporting
confidence: 61%
“…This pat-tern of decreased seed germination was observed when herbicides were applied late season but before seed physiological maturity (Azlin and McWhorter 1981;Whigham and Stoller 1979). Previous studies have shown that glyphosate, when applied to plants during seed fill, inhibits seed development by reducing the supply of aromatic amino acids (Cerdeira et al 1985). Similar studies, to our knowledge, have not been conducted for cyclohexanedione herbicides.…”
Section: Seed Yieldsupporting
confidence: 61%
“…Furthermore, the histological abnormalities seen in the embryo and endosperm indicated the inability of their cells to divide. Such effects on cell division and cell elongation were similar to those of other herbicides (Cerdeira et al, 1985;Maun & Cavers, 1969;Isaacs et al, 1989). In addition, the glyphosate might also bring about a more inclusive effect of desiccation which would prevent the functioning of all metabolic activity, including cell division and cell elongation (Cole, 1985;Cole et al, 1983;Cerdeira et al, 1985).…”
Section: Discussionmentioning
confidence: 76%
“…Wilson and Smith ( 2002 ) report that glufosinate, paraquat, and diquat applied as desiccants to common bean accelerated seed maturity and desiccation. Glyphosate applied as a desiccant reduced pod length and seed weight when used as a harvest aid in cowpea ( Vigna unguiculata L.) (Cedeira et al, 1985 ). Many studies report reduced soybean yield and seed quality as a result of the application of desiccant prior to crop maturity (Azlin and Mcwhorter, 1981 ; Cerkauskas et al, 1982 ; Boudreaux and Griffin, 2011 ).…”
Section: Discussionmentioning
confidence: 99%